1999
DOI: 10.1177/155005949903000203
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sleep Spindles in Young Children and Adolescents

Abstract: The development of sleep spindles was studied quantitatively in 32 healthy subjects between the ages of 4 and 24 years. The peak frequency distribution of the spindles showed a bimodal pattern with 11.0 to 12.75 Hz in the frontal area and 12.5 to 14.5 Hz in the centroparietal area. The two types of spindle activity showed different courses of maturation. The peak frequency of the centroparietal spindles gradually increased linearly with age, whereas the frontal spindles abruptly increased in frequency during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
83
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 14 publications
13
83
0
1
Order By: Relevance
“…Slow spindles dominate over frontal EEG derivations and are thought to involve the superior frontal gyrus, while fast spindles show up stronger in central and parietal EEG derivations and are thought to involve the precuneus, hippocampus, medial frontal cortex, and sensorimotor areas (Schabus et al, 2007; Dehghani et al, 2011). Relevant to the present study, the topographic representation of sleep spindles change with age (Tanguay et al, 1975; Shinomiya et al, 1999). Frontal spindles are more prominent in younger children while older children show more centroparietal spindles (Shinomiya et al, 1999).…”
Section: Introductionmentioning
confidence: 51%
“…Slow spindles dominate over frontal EEG derivations and are thought to involve the superior frontal gyrus, while fast spindles show up stronger in central and parietal EEG derivations and are thought to involve the precuneus, hippocampus, medial frontal cortex, and sensorimotor areas (Schabus et al, 2007; Dehghani et al, 2011). Relevant to the present study, the topographic representation of sleep spindles change with age (Tanguay et al, 1975; Shinomiya et al, 1999). Frontal spindles are more prominent in younger children while older children show more centroparietal spindles (Shinomiya et al, 1999).…”
Section: Introductionmentioning
confidence: 51%
“…However, assessing automated spindles detection, specifically in childhood, seems important as spindles show modification in amplitude, frequency, length, density, interspindle interval and topological distribution from infancy to adolescence (Nagata et al, 1996;Shinomiya et al, 1999;Scholle et al, 2007); therefore, automated algorithms should be able to adapt to those variations. Published spindle detection algorithms in children and in infants are based on empirical-mode decomposition and Hilbert-Huang transform (Causa et al, 2010), expert procedure and fuzzy logic (Held et al, 2004(Held et al, , 2006, peak identification , merge neural gas model (Estévez et al, 2007), and neuro fuzzy approach .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that different types of spindles appear to reflect neuronal networks that react differentially to age-related changes, developmental maturation changes, circadian factors, pharmacological agents and homeostatic changes (Dijk and Czeisler, 1995;Landolt et al, 1996;Shinomiya et al, 1999).…”
Section: Introductionmentioning
confidence: 99%